A Design and Implementation of Version Model in Object-Oriented Databases - Yazid, Zulkifli (1997)
Due to the advances in computer technology, new applications such as office automation, software engineering and computer aided design (CAD) have emerged.These new applications not only demand fast retrieval and modification as the earlier applications but also new requirements, for in stance, the capability to represent complex object.Many approaches have been proposed in order to meet the new requirements. It is claimed that Object- oriented Database Management System s (OODBMSs) offer a good solution. One of OODBMSs' facilitiesis the version control management. With a version control management, the management and control of object versions can be done in a systematic way.